2022
DOI: 10.1021/acsanm.2c03250
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptide Nano-assemblies with pH-Triggered Shape Transformation for Antibacterial Therapy

Abstract: Peptide-based supramolecular nano-assemblies have received much attention due to their importance in drug delivery, therapeutics, and tissue regeneration. Recent developments in dynamic self-assembly have shifted the emphasis toward producing novel nanostructures with stimuli-responsive assembly behavior. Here, we report the fabrication of a bio-nano construct with dual functionality and environmental tunability, offering advancements in wound healing applications. In particular, we have utilized a collagen-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…The biocompatible nature of the peptide itself and the mineralized peptide was assessed via the MTT reduction assay. 87 As reported in our earlier study, the positively charged peptide showed a compatible nature (∼100% cell viability) with the fibroblast cells at different peptide concentrations. 53 Interestingly, the positively charged peptide showed similar compatible nature with osteoblast cells up to 7 days of incubation.…”
Section: ■ Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The biocompatible nature of the peptide itself and the mineralized peptide was assessed via the MTT reduction assay. 87 As reported in our earlier study, the positively charged peptide showed a compatible nature (∼100% cell viability) with the fibroblast cells at different peptide concentrations. 53 Interestingly, the positively charged peptide showed similar compatible nature with osteoblast cells up to 7 days of incubation.…”
Section: ■ Introductionsupporting
confidence: 73%
“…At this point, we were curious to check the biocompatible nature of the collagen-inspired peptide and the effect of the mineralized peptide on two different osteoblast cell lines (7F2 and Saos-2). The biocompatible nature of the peptide itself and the mineralized peptide was assessed via the MTT reduction assay . As reported in our earlier study, the positively charged peptide showed a compatible nature (∼100% cell viability) with the fibroblast cells at different peptide concentrations …”
Section: Resultsmentioning
confidence: 61%
“…1c). 57 While all of the three types above undergo stimulus-triggered conversion of precursors to monomers, the target-induced self-assembly type directly uses peptide monomers, whose in situ self-assembly is initiated by targeted accumulation in bacterial membranes or specific organelles (Fig. 1d).…”
Section: Molecular Design Principlementioning
confidence: 99%
“…Reproduced with permission. 57 Copyright 2022, American Chemical Society. (d) Representative example of target-induced self-assembly.…”
Section: Gaolin Liangmentioning
confidence: 99%
“…Driven by noncovalent interactions, peptide self-assembly has received considerable attention for its wide biomedical applications including cancer and bacterial therapy, tissue engineering, immune modulation, , and drug delivery. In this work, we utilized a de novo designed self-assembling peptide to construct a bacterium trapping system with high strain selectivity. As shown in Figure , the designed molecule N-K10 contains a binding domain, a linker, and a self-assembling motif.…”
Section: Introductionmentioning
confidence: 99%